Analisis Tingkat Kerentanan Sosial Masyrakat dan Kelembagaan Terhadap Banjir di Nagari Palangai Gadang Kecamatan Ranah Pesisir, Kabupaten Pesisir Selatan: Penelitian - Anisa Yudita; Valefy Siregar; Rani Kartika; Annisa Putri (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The vulnerability of an area to disasters can be a benchmark in designing disaster mitigation. This study aims to determine the level of social vulnerability of the community and institutions to flood disasters in Nagari Palangai Gadang, Ranah Pesisir District, Pesisir Selatan Regency. This study uses a qualitative approach with data collection techniques through observation, in-depth interviews with 35 respondents and secondary data documentation. The results of the analysis show that the level of social vulnerability is High (1.762) and the level of institutional vulnerability (1.242). This condition is influenced by low income levels, economic dependence on the agricultural sector, minimal community literacy about disasters and the lack of role of local institutions in reducing the risk of flood disasters.